Evaluation of the cytotoxicity and genotoxicity of ingested titanium dioxide nanomaterials in intestinal cells - Gramacho, Ana Catarina (2020)
Many products already available, namely in agriculture and food, contain nanomaterials (NMs) and thus human ingestion of these compounds is probable through consumer products or food chain. Although NMs have been extensively investigated in recent years, the studies have generated contradictory results, possibly due to differences in the physicochemical properties of the NMs studied and to other variables in the tested systems. Furthermore, the NMs properties have been recognized as being context-dependent, i.e. can be affected by the surrounding matrix. These secondary features may be potentially more relevant for determining the toxicological outcome. In particular, processes like digestion may modify the NMs characteristics leading to unexpected toxicity in intestine cells. This work aimed to investigate the nano-bio interactions of titanium dioxide NMs (from Joint Research Centre, Ispra) in the context of intestinal tract and digestion processes, to better understand key events that may be linked to an adverse outcome pathway (AOP). In vitro for digestion was simulated and the NMs secondary properties in the intestinal cell moiety were characterized after this process. The cytotoxic and genotoxic effects of digested NMs were determined after the in vitro exposure of human intestinal cells (Caco-2). In addition, the FPG-comet assay was used to analyze oxidative DNA lesions. The digestion products without the NM showed cytotoxic effects above the concentration of 10% in cell culture medium, leading to the need to reduce its concentration below this level. Therefore, initial dose-range studies set a working range of NM concentrations of 0.14 up to 14 µg/ml (0.5-4.5 % of digestion product), which relates also with the predicted levels of exposure of human intestinal cells in real life conditions. Under these conditions, the preliminary results suggest that the tested titanium dioxide NMs do not yield cytotoxic or genotoxic effects upon 24h of exposure of Caco-2 cells, directly after the digestion process. Future studies will investigate the subcellular localization of NMs, integrity of cell junctions, activation of stress signaling pathways and secretion of inflammatory cytokines, to allow an integrated approach to potential adverse effects of the NMs. By elucidating key events elicited by NMs, linking exposure to adverse outcomes, it is expected to contribute to the safety evaluation of NMs within an AOP landscape.